Science-based criteria to identify talent among triathlon athletes - Cejuela, R.; Ferriz-Valero, A.; Selles-Pérez, S. (Triathlon Medicine, 2019)
Talent identification programmes aim at screening athletes ready to receive extra support to maximize their performance. This identification can be conventional or genetic. Factors related to performance in adult triathletes have been studied at length for decades. However, there is a shortage of literature on performance factors in young triathletes who have different physical, psychological, social and competitive characteristics. Generally, talent is identified between the ages of 6 and 15 years depending on the sport. In addition, aspects such as relative age, maturation, anthropometric characteristics and peak shape must be considered to conduct conventional comparisons between athletes. In this chapter, five are factors that are considered important for the development of talent in triathletes: sports specialization in triathlon, relative age in triathlon, optimal morphology of triathletes, physical and physiological factors and performance indicator in triathlon.